Influence of low methoxyl pectin gel textures and in vitro release of rutin from calcium pectinate beads - Pensak Jantrawut (2018)
This study described the preparation and characterization of low methoxyl pectin (LMP) gels and beads for controlled release applications. The rheological characterization of the various formulations was proposed. Then the mechanical and morphological characterizations of beads were determined. Finally, the controlled release studies taking rutin as a model drug was evaluated. The results showed that Young's modulus values of non-amidated LMP gels decrease when adding up to 15% sorbitol. Calcium pectinate beads loaded with rutin are about 600 μm, oblong shaped with dense matrix. Beads containing sodium bicarbonate showed about 80% lower rutin encapsulation efficiency by increasing the pH of the crosslinking solution. The rutin loaded in non-amidated pectinate beads containing 15% sorbitol showed the best release efficiency and swelling behavior. Therefore, the gel texture affects the release rate of the active compounds encapsulated in calcium pectinate beads and can be used as a parameter to modulate drug release. © 2013 Elsevier Ltd. All rights reserved.